1996
DOI: 10.1111/j.1440-1746.1996.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological study on combined hepatocellular and cholangiocarcinoma

Abstract: We clinicopathologically studied 23 surgically resected cases of combined hepatocellular and cholangiocarcinoma (HCC-CC). The frequency of this cancer in our subjects, who had primary liver cancer and who underwent hepatectomy, was 6.3%. The mean age of patients was 64.0 years old and the male: female ratio was 1.9:1. Serum alpha-fetoprotein was positive in 70% of cases and its levels were relatively low (< or = 1000 ng/mL) in most cases. The positive rate of serum carcinoembryonic antigen was 18% and its leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 12 publications
5
113
2
Order By: Relevance
“…10 These pathological and clinical features could be explained by a common protein network with AFP expression. Taking annexin A1 as an example, this protein is a major substrate for tyrosine kinases such as epidermal growth factor receptor and serine/threonine kinases such as protein kinase C 43,44 and has been implicated in cellular signal transduction. 45 Enhanced expression of annexin A1 was observed in poorly differentiated HCC tissues compared with their well-differentiated counterparts, and the nontumorous region contained significantly lower amounts of annexin A1, suggesting that annexin A1 is related to the histological grade of HCC and is involved in the malignant transformation process.…”
Section: Discussionmentioning
confidence: 99%
“…10 These pathological and clinical features could be explained by a common protein network with AFP expression. Taking annexin A1 as an example, this protein is a major substrate for tyrosine kinases such as epidermal growth factor receptor and serine/threonine kinases such as protein kinase C 43,44 and has been implicated in cellular signal transduction. 45 Enhanced expression of annexin A1 was observed in poorly differentiated HCC tissues compared with their well-differentiated counterparts, and the nontumorous region contained significantly lower amounts of annexin A1, suggesting that annexin A1 is related to the histological grade of HCC and is involved in the malignant transformation process.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been a few reported cases in the literature of combined hepatocellular-cholangiocarcinomas (CHCs) [1 -4], a subset of primary liver carcinomas suggested to arise from transformed progenitor cells which have the bipotential to differentiate into both hepatocytes and cholangiocytes. Taguchi et al [3] classified CHC into three types: (i) type I, in which there were clearly separable areas of HCC and CC; (ii) type II, in which the HCC and CC areas were contiguous with an intervening area of transition; and (iii) type III, in which the tumor was not readily classifiable as HCC or CC, and were composed of tumor cells showing morphological features intermediate between HCC and CC. Robrechts et al [5] reported a case of 'liver tumor of intermediate (hepatocyte-bile duct cell) phenotype', consisting of small cells with a phenotype intermediate between hepatocytes and cholangiocytes and simultaneously expressing cytokeratins (CK) 7, 8, 18 and 19.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan and east Asia, chronic HCV infection has been linked to a high incidence of ICC, including combined hepato-cholangiocellular carcinoma (c-HCC-CC) (Tomimatsu et al, 1993;Shin et al, 1996;Su et al, 1996;Taguchi et al, 1996;Yamamoto et al, 1998). Follow-up of patients with HCV infection therefore can detect many cases of ICC as well as HCC.…”
mentioning
confidence: 99%